PERAN KECERDASAN BUATAN (AI) DAN MANAJEMEN POAC DALAM MENGEMBANGKAN MUTU MODUL AJAR: STUDI KASUS DI SDN RAHARJA KAB. PURWAKARTA - Waska Warta; Andris Hadiansyah; Rosmalasari, Dewi; Wily Aulia Rahman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study investigates the strategic role of generative Artificial Intelligence (AI) in enhancing the quality of teaching modules (Modul Ajar) under the Merdeka Curriculum at SDN Raharja, a Sekolah Penggerak in Purwakarta. Grounded in George R. Terry’s POAC (Planning, Organizing, Actuating, Controlling) management theory, this qualitative case study evaluates the managerial efficacy of integrating AI into pedagogical preparation. Data were collected through observation, document analysis, and interviews with the seven teaching staff members. Findings reveal a technological adoption dichotomy: six educators successfully utilized AI to optimize instructional design, create differentiated assessments, and align learning outcomes efficiently. However, one senior teacher exhibited technological resistance due to advanced age, cognitive overload, and technostress. The POAC implementation demonstrates that while AI substantially improves administrative efficiency and pedagogical creativity, its success relies heavily on adaptive leadership, peer-mentoring, and strict controlling to mitigate AI hallucinations and ensure alignment with local wisdom. The study concludes that a strategically managed, empathetic approach is essential to bridge the digital divide among aging educators, ensuring equitable technology integration in primary education.